Enhancing Islamic banking and finance in Southeast Asia through the application of artificial intelligence: An exploration of banking's best practices - Mohd. Zain, Nor Razinah; Hassan, Rusni; Ismail, Azman (IGI Global, 2019)
The disruption of innovations in the banking sector continues to indicate a positive trend among bankers and customers. The innovations of technology that stand with speediness and fast track transaction effectively support the spread in using banking system without barriers. Recently, the financial services industry continues to be surprised by the latest technology's innovation that is known as artificial intelligence. By looking into the ecosystem for the future sustainability of Islamic banking and finance in Southeast Asia, Islamic financial services may learn and adopt several best practices of A.I. from global banking practices. With a focus on the Islamic financial services industry in Southeast Asia, an exploration on the readiness of such industry and advantages of artificial intelligence are made. This research depends on the qualitative investigation from documentary materials. The leadership of Islamic banks shows their readiness in accepting artificial intelligence